Mahasiswa Universitas Simalungun Program Studi Ekonomi Pembangunan 2020 Konsentrasi Ekonomi Sumber Daya Melakukan Observasi Lapangan di Desa Wisata Dokan, Kecamatan Merek, Kabupaten Karo, Sumatera Utara - Armitha Silalahi; Mifthahul Jannah; Rika Ardhana; Samyel Saragih; Fernaendy Girsang; Dian G. Purba (Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2023)
North Sumatra province has many historical and cultural tours that are no less interesting. For example, traditional villages or tourist villages that offer local culture and history as their main attraction. One of the most well-known traditional villages in North Sumatra province is Dokan Village in Karo District. This village has various cultural and historical heritages of the people who still uphold the teachings of their ancestors. The purpose of this service is to find out how far the development of Dokan village has been from year to year. To find out the advantages of Dokan village in terms of natural resources or human resources.